2015
DOI: 10.1016/j.infbeh.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Young adults’ reactions to infant crying

Abstract: Negative emotions and cognitive disturbances may be general adult responses to infant crying that are not limited to parents. These results suggest a broadly present human emotional and cognitive response to infant crying, that may underlie a general predisposition to care for infants in distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
(15 reference statements)
3
8
0
Order By: Relevance
“…Our behavior findings are consistent with prior work on the interfering effects of infant cries on attention and working memory [ 22 – 24 ]. It should be noted that the magnitude of the cry interference effect on Stroop performance was relatively small (mean cry–laugh blocks = 28 ms) compared to the magnitude of the Stroop interference effect (mean incongruent–congruent trials = 98 ms).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our behavior findings are consistent with prior work on the interfering effects of infant cries on attention and working memory [ 22 – 24 ]. It should be noted that the magnitude of the cry interference effect on Stroop performance was relatively small (mean cry–laugh blocks = 28 ms) compared to the magnitude of the Stroop interference effect (mean incongruent–congruent trials = 98 ms).…”
Section: Discussionsupporting
confidence: 91%
“…as well as to control sounds; participants were more distracted when listening to attachment vocalizations than to control sounds, regardless of gender or parental status. More recently, Hechler, Beijers, & de Weerth [ 24 ] showed that participants made the most mistakes on a working memory task when listening to infant crying, compared to other disturbing noises. Although much work has shown an attention bias to infant vocal stimuli, in which the power of infant vocalizations to grab attention subsequently interferes with information processing, the more specific types of neurocognitive processes affected by this attention bias to infants have remained elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Our working memory task showed that expectant parents performed worse when exposed to infant crying as compared to silence, indicating cognitive interference by infant crying. These results are similar to what we found previously in a student sample (Hechler et al, 2015). In the present study, cognitive interference by infant crying failed to predict postnatal caregiving quality.…”
supporting
confidence: 93%
“…Additionally, the results showed that the difficulty of the memory task was significantly greater with the tone compared to infant crying. This was an unexpected result as previous research22 reported that participants had the least correct trials on the working memory task when hearing infant crying compared to other noises. Although we cannot convincingly explain this result, the purpose of using the tone was simply to prevent participants from habituating themselves to repetitive infant crying and it was unlikely that the result influenced the following main results.…”
Section: Resultsmentioning
confidence: 53%